2024
DOI: 10.1371/journal.pbio.3002463
|View full text |Cite
|
Sign up to set email alerts
|

Combined analyses of within-host SARS-CoV-2 viral kinetics and information on past exposures to the virus in a human cohort identifies intrinsic differences of Omicron and Delta variants

Timothy W. Russell,
Hermaleigh Townsley,
Sam Abbott
et al.

Abstract: The emergence of successive Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) variants of concern (VOCs) during 2020 to 2022, each exhibiting increased epidemic growth relative to earlier circulating variants, has created a need to understand the drivers of such growth. However, both pathogen biology and changing host characteristics—such as varying levels of immunity—can combine to influence replication and transmission of SARS-CoV-2 within and between hosts. Disentangling the role of variant and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…This preference could be associated with specific mutations which may have causal effects on intracellular viral replication dynamics in different host cell types. Recent studies indicated that BA.2 infections were characterized by a higher peak viral load, as shown in [39–41]. This is consistent with our analysis, where we found that SNPs associated with an increase in viral copies were linked to BA.2 infections.…”
Section: Discussionsupporting
confidence: 93%
“…This preference could be associated with specific mutations which may have causal effects on intracellular viral replication dynamics in different host cell types. Recent studies indicated that BA.2 infections were characterized by a higher peak viral load, as shown in [39–41]. This is consistent with our analysis, where we found that SNPs associated with an increase in viral copies were linked to BA.2 infections.…”
Section: Discussionsupporting
confidence: 93%
“…As such, their results compare viral load measurements for Delta and Omicron infections regardless of date of symptom onset, with measurements likely to have been taken at different timepoints of individual virus dynamics trajectories. A recent study of Delta and Omicron viral kinetics accounting for time since last infection or vaccination reported higher peak viral loads for Delta infections compared to Omicron (BA.1), similar to our results [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…By accessing these large databases, it was possible to identify individuals tested multiple times and generate longitudinal follow-ups with less accuracy than the NBA one but covering a more general population. One of the outcomes of these population follow-ups was the dierence in virus kinetics between variants [154,155]. These results should be handled with care, especially when comparing studies, because contrarily to HIV where the virus load can be estimated carefully, in the case of SARS-CoV-2 the volume sampled is highly variable and the specicities of the virus life cycle, e.g.…”
Section: From Game-changing Vaccines To Immune Escapementioning
confidence: 99%